A composite disease activity index for early drug development in ulcerative colitis: development and validation of the UC-100 score. (January 2019) - Jairath, Vipul; Jeyarajah, Jenny; Zou, Guangyong; Parker, Claire E; Olson, Allan; Khanna, Reena; D'Haens, Geert R; Sandborn, William J; Feagan, Brian G
Summary: Background: Combining clinical, endoscopic, and histological data associated with ulcerative colitis disease activity in a composite index could be a more sensitive way to detect efficacy in small numbers of patients during early drug development. Our aim was to derive and externally validate a novel index for this purpose. Methods: Index development was done with data from a phase 2 placebo-controlled trial of ozanimod in patients with moderate-to-severe ulcerative colitis (n=179). Multivariable logistic regression modelling determined associations between candidate index items and absence of rectal bleeding (Mayo Clinic rectal bleeding subscore of 0), with items with a p value of less than 0·10 being taken forward into the final model. Model fit was internally validated and then externally validated in an independent phase 2 clinical trial dataset (MLN02, n=146) by measuring the area under the curve of the receiver operating characteristic (AUROC). Findings: In the derivation cohort, multivariable analysis indicated that the Mayo Clinic stool frequency subscore (odds ratio [OR] 0·43, 95% CI 0·30–0·61; p<0·0001) and the Robarts histopathology index (0·97, 0·93–1·01; p=0·09) were associated with absence of rectal bleeding. Although the Mayo Clinic endoscopic subscore was not significantly associated with rectal bleeding in multivariable analysis (0·74, 0·43–1·27; p=0·27), it was entered into the final model on the basis of the established diagnostic and prognostic significance of endoscopic findings. With these parameters, we established the composite UC-100 score (1 + 16 × Mayo Clinic stool frequency subscore [0 to 3] + 6 × Mayo Clinic endoscopic subscore [0 to 3] + 1 × Robarts histopathology index score [0 to 33]), which ranges from 1 (no disease activity) to 100 (severe disease activity). The UC-100 score strongly discriminated absence of rectal bleeding in both the development (AUROC 0·82, 95% CI 0·75–0·88) and validation cohorts (0·86, 0·80–0·92). A UC-100 score of 25 or less corresponds to a 95% probability of absence of rectal bleeding. Interpretation: We have developed and validated a novel composite disease activity index (the UC-100 score) with good discriminative performance that could used in early phase trials of ulcerative colitis. Funding: None.